Analysis of Islamic Spirituality in the Workplace and Islamic Work Ethics on OCB (Organizational Citizenship Behavior) in an Islamic Perspective - Pasaribu, Desty Maulina; Suhariadi, Fendy; Handoyo, Seger (Psikoborneo: Jurnal Ilmiah Psikologi, 2023)
The aim from this study is to analyze the effect of Islamic spirituality in the workplace and Islamic work ethics on organizational citizenship behavior from Islamic Perspective. Respondents of this study are 150 teachers of Islamic school X in Sidoarjo. This study used convenience sampling or accidental sampling This study uses an organizational citizenship behavior scale from Islamic perspectives adapted to the reliability of 0.760, the scale of Islamic spirituality in the workplace with reliability of 0.8243 and 0.9297, the scale of Islamic work ethics with a reliability of 0.881. This study uses Partial Least Square method for data analysis. It showed that there was a significant and positive influence of Islamic spirituality in the workplace and Islamic work ethics on organizational citizenship behavior from Islamic perspective on Islamic school teachers. Islamic spirituality in the workplace with the dimension of religiosity is the biggest influence in influencing organizational citizenship behavior from Islamic perspective. The results of this study are expected to add to the study of the knowledge of organizational citizenship behavior in an Islamic perspective which is still relatively new. Besides that, it can also be used as a reference for schools in improving organizational citizenship behavior in an Islamic perspective for teachers. In the end, this behavior can have a positive impact on the organization in increasing organizational effectiveness.Analisis pengaruh spiritualitas Islam di tempat kerja dan etika kerja Islam terhadap organizational citizenship behavior dalam perspektif Islam merupakan tujuan dari penelitian ini. Responden penelitian ini adalah 150 guru sekolah Islam X di Sidoarjo. Convenience sampling atau accidental sampling merupakan teknik sampling yang digunakan pada penelitian ini. Penelitian ini menggunakan skala organizational citizenship behavior Islamic perspectives yang diadaptasi dengan reliabilitas 0.760, skala Islamic spirituality in the workplace dengan reliabilitas 0.8243 dan 0.9297, skala Islamic work ethics dengan reliabilitas sebesar 0.881. Analisis data kali ini dengan teknik analisis Partial Least Square. Hasil yang didapatkan terdapat pengaruh yang signifikan dan positif dari Islamic spirituality di tempat kerja dan Islamic work ethics terhadap organizational citizenship behavior dalam perspektif Islam pada guru sekolah Islam. Adapun variabel yang paling memengaruhi organizational citizenship behavior dalam perspektif Islam adalah Islamic spirituality di tempat kerja dengan dimensi religiosity sebagai dimensi yang memiliki pengaruh terbesar dibandingkan dengan dimensi yang lain. Hasil penelitian ini dapat menambah kajian ilmu dari organizational citizenship behavior dalam perspektif Islam yang masih relatif baru. Selain itu juga dapat dijadikan referensi bagi pihak sekolah dalam meningkatkan organizational citizenship behavior dalam perspektif Islam bagi guru. Pada akhirnya, perilaku ini dapat memberikan dampak positif bagi organisasi Islam yangkatkan efektivitas organisasi.